Female Soccer Players at High Risk of Injury Maintain Improved Knee Abduction Load Six Months After Neuromuscular Training Program - Jeffrey B. Taylor; Thomas J. Hockenjos; Anh-Dung Nguyen; Audrey E. Westbrook; Mark V. Paterno; Brett S. Pexa; Kevin R. Ford (Journal of Orthopaedic & Sports Physical Therapy, 2026)
OBJECTIVE: To estimate immediate and long-term (retention) improvements in knee abduction moment (KAM) following a neuromuscular training (NMT) program with augmented biofeedback in individuals at high and low risk for injury. DESIGN: Secondary analysis of a randomized controlled trial. METHODS: One hundred fifty adolescent female soccer players were enrolled in a 6-week NMT program and randomized to biofeedback training groups: NMT+Hip-focus, NMT+Knee-focus, or NMT with a sham biofeedback. NMT was completed 3 times each week with augmented biofeedback delivered once per week. Standard 3D motion analysis of a drop vertical jump over artificial turf with embedded force platforms was performed at baseline (PRE), immediately following training (POST), and 6-months post-training (RET). Baseline measures of KAM were used to stratify participants into low- (n = 87, 12.7±2.2yrs, 153.0±11.4cm, 47.2±11.8kg) and high-risk (n = 44, 14.0±1.8yrs, 161.6±5.8cm, 53.5±9.2kg) groups, based on a previously determined cut point. A mixed-design ANOVA with between group factors of risk (High, Low) and training group (NMT+H, NMT+K, NMT), and a repeated within group factor of session (PRE, POST, RET) were used for the analysis. RESULTS: A significant interaction was identified between risk and session (p